Answer:
Jim's claim is correct
Step-by-step explanation:
Total survey=100 people
Morning exercise=35 people
Afternoon exercise=45 people
Night exercise=20 people
Morning exercise : Total survey
=35 : 100
Afternoon exercise : Total survey
=45 : 100
Night exercise : Total survey
=20 : 100
Jim's claim is correct because in finding the ratio, one has to relate it with the total people involved in the survey.
Tara's claim however seems to relate one variable with two other variables
Example:
35 : 55
Morning exercise : (morning exercise + night exercise)
35 : (35+20)
35 : 55
The answer is below
![\frac{dy}{dx} = \frac{1}{2} (x - 6)](https://tex.z-dn.net/?f=%20%5Cfrac%7Bdy%7D%7Bdx%7D%20%3D%20%5Cfrac%7B1%7D%7B2%7D%20%28x%20-%206%29)
multiply both sides by dx
![dy = \frac{1}{2} (x - 6)dx](https://tex.z-dn.net/?f=dy%20%3D%20%5Cfrac%7B1%7D%7B2%7D%20%28x%20-%206%29dx)
integrate both sides of the diffrential
![integral \: dy = integral \: \frac{1}{2} (x - 6)dx](https://tex.z-dn.net/?f=integral%20%5C%3A%20dy%20%3D%20integral%20%5C%3A%20%5Cfrac%7B1%7D%7B2%7D%20%28x%20-%206%29dx)
simplify and integrate to get y alone don't forget to tack on c with your indefinite integral
Answer: 6
Step-by-step explanation: To find the side length of a square, you need to find the square root of the area because the side length squared is the area.
Answer:
x = - 6 or x = 2
Step-by-step explanation:
The absolute value function always returns a positive value. However, the expression inside can be positive or negative.
Given
| 2x + 4 | - 1 = 7 ( add 1 to both sides )
| 2x + 4 | = 8, thus
2x + 4 = 8 ( subtract 4 from both sides )
2x = 4 ( divide both sides by 2 )
x = 2
OR
-(2x + 4) = 8
- 2x - 4 = 8 ( add 4 to both sides )
- 2x = 12 ( divide both sides by - 2 )
x = - 6
As a check
Substitute these values into the left side of the equation and if equal to the right side then they are the solutions.
x = 2 → | 4 + 4 | - 1 = | 8 | - 1 = 8 - 1 = 7 ← True
x = - 6 → | - 12 + 4 | - 1 = | - 8 | - 1 = 8 - 1 = 7 ← True
Hence the solutions are x = - 6 or x = 2
Answer:
Step-by-step explanation:
a. 5/2 ÷ 1/2 =
b. 6/9 ÷ 5/6
c. 3/6 ÷ 2/5
d. 7 1/2 ÷ 6
=
e. 1 1/3 ÷ 1 2/3=
- 4/3 ÷ 5/3 =
- 4/3 * 3/5 =
- 4/5